(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This paper delves into the life and philosophical contributions of Abdulqadir Bedil, a prominent Persian poet, writer, and philosopher whose works continue to shape literary and philosophical discourse. His focus on human spirituality and consciousness, intertwined with his unique interpretations of Persian, Indian, and Islamic thought, created a profound legacy that has inspired scholars and artists for centuries. The paper explores Bedil’s early influences, including his exposure to Sufism and Hindu philosophy, and how these elements shaped his literary output. Special attention is given to his concept of "Sukhan" (speech or language) and its role in his philosophical exploration of the human soul, nature, and the universe. The paper also examines the philosophical roots of Bedil’s ideas in Indian texts such as the "Upanishads" and "Mahabharata" and their reinterpretation within Bedil’s context. Through empirical analysis and literary examination, the paper highlights how Bedil’s approach to meaning and language parallels postmodern linguistic theory, emphasizing the fluid and evolving nature of meaning.